1998
DOI: 10.1677/joe.0.1590035
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglutethimide suppresses adrenocorticotropin receptor expression in the NCI-h295 adrenocortical tumor cell line

Abstract: The adrenostatic compound aminoglutethimide (AG), a potent inhibitor of the P450 side chain cleavage enzyme, is used in the treatment of ACTH-dependent or adrenal Cushing's syndrome. Recently, AG has been shown to inhibit ACTH receptor (ACTH-R) mRNA expression in ovine adrenocortical cells in a time-dependent fashion. To investigate whether ACTH-R down-regulation will also be induced in tumor cells, we studied the effect of AG on ACTH-R expression in the human NCI-h295 adrenocortical carcinoma cell line, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
3
14
2
Order By: Relevance
“…Fassnacht et al described a similar, but more profound effect on ACTH receptor mRNA expression (21). The expression of StAR mRNA was not changed by incubation with either aminoglutethimide or metyrapone in our experiments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Fassnacht et al described a similar, but more profound effect on ACTH receptor mRNA expression (21). The expression of StAR mRNA was not changed by incubation with either aminoglutethimide or metyrapone in our experiments.…”
Section: Discussionsupporting
confidence: 80%
“…We have previously noted that the endocrine profile and the pattern of P450 enzyme expression of the NCI-h295 cell line changes during long-term culture conditions due to selection of different clones. With regard to P450scc expression, the NCI strain used in our experiments is known to respond well to stimulation by ACTH (21).…”
Section: Discussionmentioning
confidence: 99%
“…After ACTH stimulation, H295R cells showed biphasic patterns of DHEA-S secretion. This biphasic reaction to ACTH has been reported previously (Jefcoate et al 1987;Le Roy et al 2000) and was explained by the biphasic upand downregulation of ACTH receptors in H295R cells (Fassnacht et al 1998(Fassnacht et al ,2000. This was reproduced also in a forskolin stimulation experiment (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…In subsequent studies, we also showed a similar effect in the HAC15 cell line (Tsai et al 2014), a clone of H295R, which shows good responses to AngII and ACTH . The ability of VLDL to enhance CYP11B2 expression is not additive with a near-maximal concentration of angiotensin II (10 nM) but VLDL enhances the stimulatory effect of the cAMP pathway agonist forskolin, even at a high dose (10 µM) that causes a large increase in cAMP levels and aldosterone production in H295R cells (Fassnacht et al 1998). In addition, VLDL's stimulation of steroidogenesis was not unique to aldosterone production.…”
Section: Vldl and Aldosterone Productionmentioning
confidence: 99%